The Significance of Traditional Materials and Their Substitution with Newly Available Materials: The Effects on House Form of the Atoni Building Culture - Zamolyi, Ferenc (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2021)
This article focuses on the region of Central Timor, settled by the Atoni Meto people, who live in round houses built on the ground. There seem to have developed local peculiarities in vernacular architecture, which require the use of wooden materials of different size, shape and state of processing. Changes in local vernacular architecture were also induced by the recent availability of modern materials such as bricks, concrete and corrugated iron. The aim of this article is to explore how such building materials are used and whether they are/ can be integrated into local vernacular building traditions. Fieldwork conatining architectural survey was conducted in Timor in May 2004 in Maubesi, and in June 2011 near Soe and Nikiniki (villages None, Supul and Boti) and Kefamenanu (among others the villages of Fafenesu, Maslete and Tamkessi). Some of the materials seem to have a strong effect on the layout or design of the buildings, whereas in other cases, such effects are far more subtle. In some cases, the new materials are used to imitate the more traditional ones, with astonishing results, and often incorporating structural details from the older technology and traditional materials which are copied. New materials already influence the building due to their different, new properties, and designs are devised to adapt to these changes, which in the end result in an altered building. In other cases, there is no compatibility at all, and old forms and designs are abandoned in favour of a new concept supported by new materials.